Catching up of emerging economies: the role of capital goods imports, FDI inflows, domestic investment and absorptive capacity - Glas, Alexander; Hübler, Michael; Nunnenkamp, Peter (Applied economics letters, 2016)
We show that the impact of capital goods imports and FDI inflows on economic convergence depends on the local capacity of emerging economies to absorb superior technologies.
Published online: 07 Sep 2015
Gesehen am 18.06.2020